Synthesis and Application of Sawdust-derived Nanocellulose for Sustainable Energy Harvesting - Athwal, Shinar (Thapar Institute of Engineering and Technology, 2025)
Cellulose is the most abundant, biodegradable, and versatile material which are easily available in nature and is used as a biomaterial for various applications. To increase the applicability of cellulose, it’s mechanical, thermal, optical, and electrochemical properties are improved by converting it into nanocellulose. Moreover, nanocellulose, when derived from waste residues, not only provides materials for advanced applications (energy harvesting, environmental remediation, sensing, and storage, etc.) but also a sustainable solution to treat waste build-up in the environment. Herein, the waste sawdust is used to synthesize cellulose through alkaline hydrolysis, followed by bleaching treatment, which is further, converted into nanocellulose (NC) via physical, chemical, and biological treatments for energy harvesting. The structural and morphological analysis of synthesized cellulose and NC is done by XRD, FTIR, and SEM. The stability and particle size have been characterized by zeta potential and DLS. Next, the synthesized NC has been combined with corn starch and PVA in different ratios to fabricate a film by solvent casting, which is further characterized by using FT-IR, dielectric studies, and triboelectric studies. Further, the nanocellulose-based triboelectric nanogenerators have been designed by pairing the various composites as positive triboelectric material with the fluorinated ethylene propylene (FEP) film as the negative triboelectric material. The optimized 1 wt % NCTENG exhibits an open circuit voltage of 1kV, short-circuit current of 37 µA, and a maximum power density of 4.6 W/m2 at 107Ω of load resistance. This study facilitates the sustainable and adaptable fabrication of TENGs for many electrochemical applications, such as energy harvesting and sensors.
Keywords: Saw-dust; Nano-cellulose; Green Energy; Sustainable Energy Harvesting; Synthesis; Biodegradable